Business Travel and Behavioral and Mental Health. Issue 7 (July 2018) - Rundle, Andrew G.; Revenson, Tracey A.; Friedman, Michael
Abstract : Objective: Assess associations between business travel and behavioral and mental health. Methods: Cross-sectional analyses of de-identified electronic medical record data from EHE International, Inc. a provider of corporate wellness programs. Results: Higher levels of business travel were associated with poorer outcomes. Compared with traveling 1 to 6 nights/mo for work, those who traveled 21+ nights were more likely to: smoke (prevalence ratio [PR] = 3.74, 95% confidence interval [CI] 2.56, 5.46), report trouble sleeping (PR = 1.37, 95% CI 1.09, 1.71), be sedentary (PR = 1.95, 95% CI 1.56, 2.43), and score above clinical thresholds for alcohol dependence (CAGE score >1: PR = 2.04, 95% CI 1.26, 3.29), and mild or worse anxiety (Generalized Anxiety Scale [GAD-7] score >4: PR = 1.69, 95% CI 1.29, 2.21), and depression symptoms (Patient Health Questionnaire [PHQ-9] score >4: PR = 2.27, 95% CI 1.70, 3.03). Conclusions: Employers should provide programs to help employees manage stress and maintain health while traveling for work.